A Rational Approach to the Design of Aerated Sewage Lagoons - Pohl, Edward F. (1970)
The use of aerated lagoons as an economical sewage treatment system is a recently developed concept. Its adaptability to arctic and subarctic environments has been established through test programs in Alaska. The report summarizes current developments and discusses the physical and biochemical parameters which must be considered during design.